ALAT PENDETEKSI TELUR MENGGUNAKAN SENSOR CAHAYA DAN BAHASA C - Hamdani, Mochammad; Affandi, Luqman; Syahminan, Syahminan (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
All this time available many manual methods those are utilized to know quality or egg chicken freshness for example utilize sunlight or flashlight for irradiates egg at dark place then see contents from egg chicken to be sorted. Same process also been done cattleman or grocer to sort chicken egg bases its quality. Utilizing manualing method to detect egg quality require time that adequately long time because detect egg chicken by piece will risk egg getting loose from hands and need so long time. The purpose of this research is for make tool detection utilizing sensor LDR (Light Dependent Resistor), LCD (Liquid Crystal Display ) and Microcontroller ATmega 8 as the processor. Performance result of this device to detect egg more or less 2 seconds/items with accuracy 87%. Performance result of this device influential from condition egg chicken is to be detected.Keyword: Egg Chicken, Microcontroller ATmega8, Sensor LDR, LCD